Imagination for change: The Post-Fossil City Contest. (April 2019) - Pelzer, Peter; Versteeg, Wytske
Highlights: There is a crisis of the imagination regarding post-fossil futures; we need to better understand how imagination could be mobilized for societal change. We analyze the Post-Fossil City Contest : an international design contest for imaginations of a city beyond carbon. We introduce the concept of 'imaginative logics': the principles by which an abstract phenomenon is made tangible. A typology of five imaginative logics is distinguished: doable, juxtaposing, defamiliarizing, guerilla and procedural. Abstract: The transition to a less carbon-dependent society is arguably one of the most pressing issues of our time. As carbon is deeply embedded in contemporary western culture, this transition requires a deep reconsideration of cultural values. Art and design can be helpful in opening up this debate and imagining alternative futures. However, not much is known about how such interventions work. In this exploratory paper, we analyse a futuring intervention in which we were closely involved as organisers and curators– the Post-Fossil City Contest. This international competition aimed at imagining a city beyond carbon received 250 entries and resulted in a public exhibition at the municipal building in Utrecht, the Netherlands. The ideas developed by the finalists of the Post-Fossil City Contest inspired us to develop the notion of ' imaginative logics' : the set of principles underlying or constituting an imaginative intervention, by means of which an abstract phenomenon is made present to the audience. Linking our empirical observations to the speculative design and experiential futures literature, we distinguish between doable, juxtaposing, defamiliarizing, guerilla and procedural imaginative logics. This typology can be a starting point for further research into how and when to apply what kind of futuring intervention.